The Autobiography of an Ex-Colored Man and The Human Stain: A Comparative Study on Two Passing Novels - Carletto, Alice (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
The main objective of this essay is to analyse and compare two novels about passing, published in the USA in different periods: James Weldon Johnson’s The Autobiography of an Ex-Colored Man (1912) and Philip Roth’s The Human Stain (2000). Thus, one of the main aims of the essay is to show how the passing motif is constructed by the main characters, therefore revealing what the reasons that led them to perform the passing phenomenon are. The essay includes an introductory part in which the passing theme is presented, and in which the main objectives are outlined. The following two sections are devoted to the analysis of the two novels. The main purpose is to describe the passing phenomenon in each novel, delving into the reasons that induce the protagonists to undertake another life, sidelining, in this way, their African American heritage. Subsequently, a concluding part will follow, in which final considerations will be drawn, and points of difference and similarities between the two characters will be underlined. This essay represents another contribution to the passing trope in literature, while also reconsidering the American ideal of freedom.